Hubungan Ketahanan Pangan dan Hygiene Sanitasi dengan Kejadian Gizi Kurang pada Balita di Puskesmas Caringin Kota Bandung - meladeraamelia (Jurnal Ilmiah Gizi dan Kesehatan (JIGK), 2025)
Undernutrition among toddlers remains a major public health concern in Indonesia. At the Caringin Health Center in Bandung City, the prevalence of undernourished children increased from 3.4% in 2024 to 4.2% in 2025. This study aimed to analyze the relationship between household food security and hygiene-sanitation with undernutrition in children under five. A quantitative case-control design was used, involving 100 children (50 cases and 50 controls) selected through non-proportional stratified sampling. Data were collected using the HFSSM and STBM questionnaires, along with anthropometric measurements based on WHO standards. The results showed that 78% of undernourished children came from food-insecure households and 70% lived in poor sanitation environments. Statistical tests revealed significant associations between food security (p=0.000; OR=6.222) and hygiene-sanitation (p=0.000; OR=9.333) and the nutritional status of children. It can be concluded that adequate food security and sanitation play a crucial role in preventing undernutrition among toddlers.